Hunting and conservation status of primates populations in the Itaya river basin, Loreto, Peru - Aquino, Rolando (2008)
This report contains information related to the diversity and hunting impact of the primates, as well as the potential threats for the populations that inhabit the upper Itaya river basin. It is based on census by transect and hunting records carried out in six communities. During the census 384 groups belonging to 9 were observed of the 11 species that inhabit the study area. Most records corresponded to Saddle-back tamarin (Saguinus fuscicollis Spix) with 25,3%, saki monkey (Pithecia aequatorialis Hershkovitz) with 20,6% and woolly monky (Lagothrix poeppigii Humboldt) with 15,9%. Population density was estimated for nine species, being the squirrel monkey (Saimiri sciureus Linnaeus) the most abundant with 18,2 individuals/km2, followed by woolly monkey (L. Poeppigii) with 15,5 individuals/km2 and saddle-back tamarin (S. fuscicollis) with 10,5 individuos/km2; the opposite occured in red howler monkey (Alouatta seniculus Linnaeus) whose density was estimated in 0,15 individuals/km2. Of the hunting area estimated in 600 km2 were harvested an annual average of 262 individuals, whose biomass was estimated in 1677,9 kg. Of them, 119 individuals equivalent to 45% corresponded to woolly monkey (L. poeppigii) whose hunting pressure was calculated in 0,19 individuos/km2. The application of the harvest model suggests overhunting in populations of red howler monkey (A. Seniculus), woolly monkey (L. Poeppigii) and brown capuchin monkey (Cebus apella). Hunting and deforestation with agricultural purpose are the potential threats for the primates populations.